2017
DOI: 10.1007/s40800-017-0049-9
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Injury After Intramuscular Administration of Diclofenac: A Case Report Supported by Magnetic Resonance Imaging

Abstract: Intramuscular injection of diclofenac is still frequently practiced, although there is ample evidence that the risk of local tissue intolerability is highly underestimated. The aim of this study was to evaluate local toxicity in a patient using magnetic resonance imaging. A patient who gave written informed consent received a medically indicated intramuscular administration of diclofenac 75 mg/2 mL. Simultaneously with magnetic resonance imaging of the depot, a clinical–chemical evaluation and quantification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 11 publications
1
10
0
1
Order By: Relevance
“…Noninvasive imaging approaches to assess LA drug distribution in humans for durations of weeks to months have been sparingly applied, because detection techniques to directly assess drug substance are not readily available 29–33 . Computed tomography has been used to assess LA injectable depot location variability between gluteal muscle and SC adipose fat and, in doing so, has been used to determine the association between BMI and IM misinjections 28,34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noninvasive imaging approaches to assess LA drug distribution in humans for durations of weeks to months have been sparingly applied, because detection techniques to directly assess drug substance are not readily available 29–33 . Computed tomography has been used to assess LA injectable depot location variability between gluteal muscle and SC adipose fat and, in doing so, has been used to determine the association between BMI and IM misinjections 28,34 .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings of cabotegravir LA drug being distributed along IM fascial planes is consistent with previous clinical observations and with our previous preclinical MRI study findings, which were confirmed using imaging mass spectroscopy showing cabotegravir LA drug colocated within interfacial planes of muscles. 12,31,33 When examining which key imaging endpoints (e.g., volume, surface area, T2-weighted, ADC) were key markers associated with drug absorption and PK exposure, the drug depot surface area assessed within 2 hours of administration was highly correlated with early plasma cabotegravir PK, C max and with partial AUC 0-4wk . This is unsurprising because insoluble drug particle dissolution rates are directly related to specific surface area of the drug particle, 36,37 and dissolution studies showing surface area of insoluble drugs used as LA injectables correlated well with in vivo drug exposure.…”
Section: Methodsmentioning
confidence: 99%
“…NSAIDs, such as diclofenac sodium, may cause cytotoxic effects by altering local pH levels and activating the preapoptotic pathways. Therefore, even a proper injection inside the musculature may cause local destruction (6,17,18). On the other hand, the necrosis mimics a perforasome as its demarcation line passes over the injection area.…”
Section: Discussionmentioning
confidence: 99%
“…Diclofenac, 2-[ (2,6-dichlorophenyl)-amino]-benzeneacetic acid, is a synthetic nonsteroidal anti-inflammatory analgesic drug [10], pharmaceutically formulated as different salts, usually as potassium and sodium. The drug is used to treat rheumatoid arthritis, osteoarthritis [22,16], musculoskeletal injuries [38], ankle sprain injuries [28,29] and is administered as post-surgery analgesic in human and veterinary medicine [23]. Many patients taking diclofenac for arthritis also need additional drugs for other chronic health problems such as hypertension [40].…”
Section: Introductionmentioning
confidence: 99%